SHAF for Mitigation of Current Harmonics Using p-q Method with PI and Fuzzy Controllers - Mikkili, S.; Panda, A. K. (Engineering, Technology & Applied Science Research, 2011)
Commencing with incandescent light bulb, every load today creates harmonics. Unfortunately, these loads vary with respect to their amount of harmonic content and response to problems caused by harmonics. Issue of Harmonics are of a greater concern to engineers, building designers and in industrial applications because they do more than distort voltage waveforms, they can overheat the building wiring, cause nuisance tripping, overheat transformer units, and cause random end-user equipment failures. Thus power quality has become more and more serious with each passing day. As a result active power filter (APF) gains much more attention due to excellent harmonic compensation. But still the performance of the active filter seems to be in contradictions with different control techniques. The main objective of this paper is to analyse shunt active filter with fuzzy and pi controllers. To carry out the analysis, we consider active and reactive power method (p-q). Extensive simulations were carried out; simulations were performed with balance, unbalanced and non sinusoidal conditions. Simulation results validate the dynamic behaviour of fuzzy logic controller over pi controller.